PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS 5 PADA PEMBELAJARAN IPAS - Annisa Amalia; Bella Silvesteria Damanik; Faizati umu Aimanah; Candra Rindi Irawan; Destrinelli; Risdalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low ability of students in learning science, especially in grade V. The research also aims to improve students' abilities in learning science by using the role playing method. This research is a Classroom Action Research (CAR) consisting of 2 cycles and each cycle consists of 4 actions, namely planning, implementation, closing and reflection. The results of the study showed that there was an increase in students' activeness in learning science through the role playing method. Of the 20 students, the student's learning completeness in cycle 1 was only 40%, but in cycle 2 it reached 75% with an average value of 73.8. The increase in student activity proves that the use of the role playing method can increase student activity in learning science, especially in the food chain material.